Amendments food waste compost on soil enzymatic activities in groundnut cultivated soil, India - J. Manikandan, T. Elavazhagan, S. Jayakumar, C. Chitravadivu, V.Balakrishnan, (Journal of Phytology, 2009)
Soil enzymes are play an important role in organic soil. Soil microbes enhances the enzymatic activities .Which is very beneficial to solubilizing the nutrients in the soil. In the present investigation was to find out the activity of soil enzymes such as acid phosphatase, alkaline phosphatase, dehydrogenase and to find the fresh weight of groundnut pods in the addition of food waste compost.